Taxonomic revision of Rhyacophila aquitanica (Trichoptera: Rhyacophilidae), based on molecular and morphological evidence and change of taxon status of Rhyacophila aquitanica ssp. carpathica to Rhyacophila carpathica stat. n. - Bálint, Miklós; Botoşaneanu, Lazare; Ujvárosi, Lujza; Popescu, Octavian (Zootaxa, 2009)
A taxonomic revision of Rhyacophila aquitanica carpathica Botoşaneanu, 1995, is proposed based on molecular results and previously described morphological differences. Genitalia of R. aquitanica McLachlan, 1879, and Rhyacophila carpathica Botoşaneanu stat. n. are redrawn here to facilitate the distinction of the two entities. While the morphological and ecological characteristics of the two species show many similarities, the nucleotide sequences of the two species are very different, even when compared to those of Rhyacophila tristis Pictet, 1834, suggesting a distant allopatric speciation event.